Enhanced Valley Polarization in WS2/LaMnO3 Heterostructure. Issue 10 (17th January 2022) - Dang, Jianchen; Yang, Mingwei; Xie, Xin; Yang, Zhen; Dai, Danjie; Zuo, Zhanchun; Wang, Can; Jin, Kuijuan; Xu, Xiulai
Abstract: Monolayer transition metal dichalcogenides have attracted great attention for potential applications in valleytronics. However, the valley polarization degree is usually not high because of the intervalley scattering. Here, a largely enhanced valley polarization up to 80% in monolayer WS2 under nonresonant excitation at 4.2 K is demonstrated using WS2 /LaMnO3 thin film heterostructure, which is much higher than that for monolayer WS2 on SiO2 /Si substrate with a valley polarization of 15%. Furthermore, the greatly enhanced valley polarization can be maintained to a high temperature of about 160 K with a valley polarization of 53%. The temperature dependence of valley polarization is strongly correlated with the thermomagnetic curve of LaMnO3, indicating an exciton–magnon coupling between WS2 and LaMnO3 . A simple model is introduced to illustrate the underlying mechanisms. The coupling of WS2 and LaMnO3 is further confirmed with an observation of two interlayer excitons with opposite valley polarizations in the heterostructure, resulting from the spin‐orbit coupling induced splitting of the conduction bands in monolayer transition metal dichalcogenides. The results provide a pathway to control the valleytronic properties of transition metal dichalcogenides by means of ferromagnetic van der Waals engineering, paving a way to practical valleytronic applications. Abstract : A largely enhanced valley polarization up to 80% is demonstrated in monolayer WS2 under a nonresonant excitation at 4.2 K using WS2 /LaMnO3 thin film heterostructure, which provides an effective pathway to control the valleytronic properties of transition metal dichalcogenides by means of ferromagnetic van der Waals engineering.